Impact of preceding workload on team performance in collegiate men's ice hockey - Neeld, K. L.; Peterson, B. J.; Dietz, C. C.; Cappaert, T. A.; Alvar, B. A. (The Journal of Strength and Conditioning Research, 2021)
Although the workload-injury relationship has received ample research attention, the relationship between prior workload and performance in team sport remains poorly understood. The purpose of this study was to determine if preceding workloads influence competition performance in men's ice hockey. On-ice workload data were collected from all players on a NCAA Division I men's ice hockey team for 2 consecutive seasons. Training and match workloads were characterized using 7 variables (player load, skating load, explosive efforts, high force strides, player load/min, skating load/min, and average stride force/lb). Team performance was calculated as the difference between the subject and opposing teams' shots on goal. Nine separate ANCOVAs were performed to assess the effect of workload across quartiles of 5 different time spans (1,3,5,7 and 28 days), and low, typical, and high zones of 4 time ratios (1/28, 3/28, 5/28, and 7/28) days) on team shot differential, accounting for season quarter and rank differential between the subject and opposing team. Alpha was set a priori to 0.05. Of all workload measures included in each analysis, only 7-day high force strides (p < 0.01, eta2 = 0.72), and 7-day player load·min-1 (p < 0.05, eta2 = 0.50) had a significant effect on shot differential. Measures of skating intensity in the week preceding competition have the largest impact on team performance. These results can be used by performance coaches to examine tests of speed, power, strength, and conditioning to identify potential limiting factors to high-intensity skating, design training programs with specific need-based emphases, and make recommendations for weekly management of high-intensity skating loads.